Sex differences in spatial learning and memory and hippocampal long-term potentiation at perforant pathway-dentate gyrus (PP-DG) synapses in Wistar rats - Safari, Samaneh; Ahmadi, Nesa; Mohammadkhani, Reihaneh; Ghahremani, Reza; Khajvand-Abedeni, Maryam; Shahidi, Siamak; Komaki, Alireza; Salehi, Iraj; Karimi, Seyed Asaad (Behavioral and brain functions, 2021)
Recent studies show that gender may have a significant impact on brain functions. However, the reports of sex effects on spatial ability and synaptic plasticity in rodents are divergent and controversial. Here spatial learning and memory was measured in male and female rats by using Morris water maze (MWM) task. Moreover, to assess sex difference in hippocampal synaptic plasticity we examined hippocampal long-term potentiation (LTP) at perforant pathway-dentate gyrus (PP-DG) synapses. In MWM task, male rats outperformed female rats, as they had significantly shorter swim distance and escape latency to find the hidden platform during training days. During spatial reference memory test, female rats spent less time and traveled less distance in the target zone. Male rats also had larger LTP at PP-DG synapses, which was evident in the high magnitude of population spike (PS) potentiation and the field excitatory post synaptic potentials (fEPSP) slope. Taken together, our results suggest that sex differences in the LTP at PP-DG synapses, possibly contribute to the observed sex difference in spatial learning and memory.